2020
DOI: 10.1186/s12866-020-02037-6
|View full text |Cite
|
Sign up to set email alerts
|

Lower methane emissions were associated with higher abundance of ruminal Prevotella in a cohort of Colombian buffalos

Abstract: Background Ruminants burp massive amounts of methane into the atmosphere and significantly contribute to the deposition of greenhouse gases and the consequent global warming. It is therefore urgent to devise strategies to mitigate ruminant’s methane emissions to alleviate climate change. Ruminal methanogenesis is accomplished by a series of methanogen archaea in the phylum Euryarchaeota, which piggyback into carbohydrate fermentation by utilizing residual hydrogen to produce methane. Abundance of methanogens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
2
28
1
Order By: Relevance
“…Although methane emission was not measured in this study, the high relative abundance of methanogenic archaea in the Fed group at T0 and T24 H is interesting, especially with regards to several reports of low methane emission rates by black soldier fly larvae ( Mertenat et al, 2019 ; Pang et al, 2020 ; Parodi et al, 2020 ). Indeed, differences in methanogen abundance would affect methane production, but it remains also possible that differences in microbial composition and functioning that result in perturbation of hydrogen metabolism or accumulation may also impact methanogenesis and methane emissions ( Sugimoto et al, 1998 ; Sollinger et al, 2018 ; Aguilar-Marin et al, 2020 ). Notwithstanding, the higher relative abundance of Methanomicrobiales in the black soldier fly larval microbiomes within the early timepoints of the Fed group could be an indication of the reduced gut environment, as well as conditions of the external (i.e., fresh substrate with very little frass) and consumed substrate (i.e., within the gut), including mixed alcohol and other products resulting from digestion and fermentation of plant polymers ( Lurie-Weinberger and Gophna, 2015 ; Moissl-Eichinger et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although methane emission was not measured in this study, the high relative abundance of methanogenic archaea in the Fed group at T0 and T24 H is interesting, especially with regards to several reports of low methane emission rates by black soldier fly larvae ( Mertenat et al, 2019 ; Pang et al, 2020 ; Parodi et al, 2020 ). Indeed, differences in methanogen abundance would affect methane production, but it remains also possible that differences in microbial composition and functioning that result in perturbation of hydrogen metabolism or accumulation may also impact methanogenesis and methane emissions ( Sugimoto et al, 1998 ; Sollinger et al, 2018 ; Aguilar-Marin et al, 2020 ). Notwithstanding, the higher relative abundance of Methanomicrobiales in the black soldier fly larval microbiomes within the early timepoints of the Fed group could be an indication of the reduced gut environment, as well as conditions of the external (i.e., fresh substrate with very little frass) and consumed substrate (i.e., within the gut), including mixed alcohol and other products resulting from digestion and fermentation of plant polymers ( Lurie-Weinberger and Gophna, 2015 ; Moissl-Eichinger et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly though, a study reported that early and late lactation stages were correlated with different levels of CH 4 emissions not accompanied by changes in the rumen microbiome [80]. In a study with Colombian buffalos, the genus Prevotella was associated with low CH 4 emissions [81]. Despite the differences reported in archaea composition between buffalo and cattle [82], this bacterial group seems relevant for CH 4 emission of both species.…”
Section: Methanogenesis and Ch 4 Emissionmentioning
confidence: 94%
“…Despite the differences reported in archaea composition between buffalo and cattle [82], this bacterial group seems relevant for CH 4 emission of both species. As some authors pointed, the host genotype affects the phenotype of CH 4 emission, in addition to its microbial community [81]. Indeed, one study indicated that H 2 -producing bacteria explained up to 24% of CH 4 phenotypic variance, and host genome, 14% [70].…”
Section: Methanogenesis and Ch 4 Emissionmentioning
confidence: 99%
“…P. ruminicola has the greatest range and activity of dipeptidyl peptidases, which release dipeptides from the N-terminus of peptides [ 43 ] and may be the main reason for the higher substrate N digestibility in S30 and S40 and also the strong positive correlation of this microbe with ND ( Figure 5 B). A recent study [ 44 ] showed that lower methane emissions and higher feed conversion efficiency were associated with a higher abundance of P. ruminicola , which was also validated from the results that substrates DMD and ND were increased in S30 and S40, while methane production requires subsequent experiments to verify. Furthermore, it was observed that the abundance of Fibrobacter_succinogenes ( F. succinogenes ), which is considered to be a key cellulolytic bacterium that promotes the metabolism of other microbiota members by degrading cellulose into soluble sugars and succinate [ 45 ], was up-regulated in S30 and S40.…”
Section: Discussionmentioning
confidence: 57%